Implementation of full-day school program management in improving the quality of student learning at the State Islamic Junior High School (MTsN) in Tarakan City - Elis Sofiyati (Journal of Education and Teaching Learning, 2026)
This study aims to analyze the implementation of the full-day school program management in improving the quality of student learning at MTsN Tarakan City. The study used a qualitative approach with field research through interviews, observation, and documentation techniques involving the principal, vice principal, teachers, education staff, and students. The results indicate that the full-day school program management has been implemented through management functions that include systematic planning, organization, implementation, and evaluation. This program has had a positive impact on improving the quality of student learning, as indicated by increased academic achievement, discipline, responsibility, active participation in learning, and social and religious skills. The successful implementation of the program is supported by the commitment of the madrasah leadership, teacher competence, parental support, the availability of facilities and infrastructure, and a conducive madrasah culture. Meanwhile, inhibiting factors identified include limited student rest time, learning fatigue, differences in student abilities, and limited supporting facilities. This study confirms that effective full-day school program management can be a crucial strategy for improving the overall quality of student learning in the madrasah environment.